The language of the Southwestern inscriptions: state-of-the-art (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2021)
Current knowledge about the language of the South-Western steles from the Iberian peninsula is reviewed in this paper. It is argued that the appropriate methodology for the study of this language should rely on a thorough internal analysis of the data provided by the inscriptions themselves, instead of jumping to hasty interpretations and etymological proposals allegedly supporting its classification as a Celtic language. Internal evidence provides relevant information about phonetics and allows for identifying possible lexemes and suffixes, which is crucial for the advancement in the understanding of this language.
Keywords: Southwestern steles; Palaeohispanic languages; Palaeohispanic scripts; Iron Age; Tartessos; Celtic languages